Stakeholders Perception for Ecotourism Development in Tesso Nilo National Park - La Ode Sabir; Ricky Avenzora; Gunardi Djoko Winarno (Media Konservasi, 2018)
The increasing issue of occupational land conflict in Tesso Nilo National Park (TNTN) should be addressed objectively by various stakeholders. One of the important things that can be done to support these efforts is to conduct careful and thorough research on the orientation of stakeholders for the implementation of ecotourism development in TNTN. The stakeholders focussed on this research consist of eight groups of respondents, namely land claiming communities, landowners, landless communities, TNTN centers, local government, forestry services, private companies and non - overnmental organizations. Data collected then analyzed by using One Score One Criteria System. The result of this study indicates that stakeholder perceptions related to various aspects of the TNTN development concept are "somewhat good" (score 5). This provides an interpretation that TNTN's development concept is "somewhat effective and efficient" to be implemented in the development of forest ecosystems in TNTN.Keywords: ecotourism, stakeholders, TNTN